Pengembangan LKPD Bermuatan Permainan Tradisional Serok Kuali pada Materi Perkalian Peserta Didik Kelas III SDN Deket Wetan Lamongan - Ristik Arini Auliya'Sari; Arissona Dia Indah Sari; Afakhrul Masub Bakhtiar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to develop Student Worksheets (LKPD) incorporating the traditional serok kuali game on multiplication material for third-grade students at SDN Deket Wetan Lamongan and to determine their validity, effectiveness, and practicality. The research method employed was Research and Development (R&D) using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects included two expert validators, namely a media expert and a subject-matter expert, as well as 15 third-grade students at SDN Deket Wetan Lamongan. Data were collected using expert validation questionnaires, conceptual understanding tests (pretest and posttest), and student response questionnaires. The results showed that the developed LKPD demonstrated a very high level of validity, with a score of 97.5% from the media expert and 95.55% from the subject-matter expert. The effectiveness test indicated an improvement in students’ learning outcomes, with an N-Gain score of 0.803 (80.3%), which falls into the effective category. In addition, students’ responses to the use of the LKPD reached a percentage of 95.6%, categorized as very good. Based on these findings, it can be concluded that the LKPD incorporating the traditional serok kuali game is feasible, effective, and practical for use as instructional material to enhance third-grade elementary school students’ understanding of multiplication concepts.